An Agent-Based System for the Design of New Products Using a Fuzzy Multicriteria Approach - Figueroa-Perez, J. Francisco; Leyva-Lopez, Juan C.; Pérez-Contreras, Edgar O.; Sánchez, Pedro J.; Ramirez-Noriega, Alan D. (International journal of fuzzy systems, 2020)
The intense competition of global markets stimulates a significant change in the way products are designed, manufactured, and delivered. Such a situation is forcing companies to consider the use of new tools to support this decision process. This paper describes an agent-based system implementing a novel consumer-based fuzzy multicriteria methodology to support the design of new products. It argues that a combination of marketing decision support systems, multicriteria and multiobjective methodologies, fuzzy models, and agent technologies could be a valuable tool to assist marketing managers in new product design applications. In the multi-agent system architecture, software agents were classified into types and organized in teams. The first includes interface, task, and information agents. The second reflects Simon’s decision-making process, including intelligence, design, and choice teams. The communication between agents is carried out using an ontology. An example of system operation attempting to get the design of new corn oil is presented using sequence diagrams.